Технологические аспекты эффективности самостоятельной деятельности студентов - Конопелько, С. И. (БНТУ, 2004)
According to our investigation we emphasize the criterion qualities and the aspects of the student's self work. The levels and the main characteristics of the student's self work are find out. The study process is continuing as the step of lifelong learning and it is undertaken with the purpose of using the outcomes to help the students to leam, to know and to understand , change themselves as person.